The Use of The Group Investigation Type of Cooperative Learning Model When Online Learning to Increase Students' Learning Motivation - Jamaluddin, Jamaluddin; Hayati, Munggarani Kusumah (Atthulab: Islamic Religion Teaching and Learning Journal, 2022)
This study aims to determine the application of the Group Investigation Type cooperative learning model to the subjects of Islamic Religious Education and Character Education in seventh-grade students at SMPN 4 Cianjur through online learning. This study used a quasi-experimental method located at SMPN 4 Cianjur. The data collection tools used were observation, interviews, tests, questionnaires, and literature studies—quantitative data analysis with a statistical approach. The results of this study are: first, the application of the group investigation type cooperative learning model to PAI and Budi Pekerti subjects in class VII SMPN 4 Cianjur with online learning is included in the particular category as indicated by the acquisition of variable X of 4.20 which is included in the interval 4.20 to 5.00. Second, the learning motivation of class VII students at SMPN 4 Cianjur is high if online learning using the group investigation type cooperative learning model is included in the high category as indicated by the acquisition of the Y variable of 3.92, namely at intervals. From 3.40 to 4.19. Third, the application of the Group Investigation type of cooperative learning model in online learning has a relationship with an increase in student motivation of 0.83 with a strong category including the interval 0.80-1.00. The significant influence of variable X on variable Y can influence or contribute 68.9%, while other factors influence the remaining 31.11%.